Effect of financial development on economy growth in Malaysia / Zulaika Zolkefli - Zolkefli, Zulaika (2018)
Financial development is a part of the private sector development approach to encourage economic growth and reduce poverty. Financial development thus involves the establishment and expansion of instruments, institutions and market that support this investment growth and process. Financial development may be defined as development in the size. efficiency and Stability and access to financial System. Basically, the of Financial Sector on overcoming cost incurred by the financial System which Channel capital to most productive useful to economy growth. The role of financial market to economy growth is to preserve the competitiveness of an economy today given the strongly increase rapid technological process and increase of innovation for growth performance. Besides that, financial sector also provide fie basic for job creation. fie objective of this study is to determine the effect of Financial Development on Economy Growth in Malaysia. GDP growth in Malaysia was used as proxy for economy growth. Broad Money and Private Sector Credit was used proxy for financial development variable. Meanwhile, Trade Openness and Gross Fixed Capital Formation were used as a control variable. Sample of this study will be obtained by using the World Flank Data. All this information will be gathered in yearly term for each variable which covering the thirty year from period 1987 to 2016. This study will be conducted by using multiple regressions. The result for this study is there is negative significant effect between Private Sector Credit and GDP in Malaysia. Meanwhile, there is no significant effect between Broad Money and GDP in Malaysia,